The Decrease of the Students’ Character during Covid 19 Pandemic: A Survey of Students in Binjai - Yuhdi, Achmad; Ayudia, Alda Marsya; Majid, Ismail; Cahyo, Ahmad Nur; Sartika, Fuji; Zulrahman, Muhammad Febrilian (Budapest International Research and Critics University, 2021)
The research in this article has purposes to describe and analyze the decrease of the students’ character values during the Covid-19 pandemic. This qualitative method study uses a qualitative descriptive approach. The data in this study are the students’ answers from questionnaires that describe behavior during online learning. The source of data in this study was the students’ questionnaires. The data collection techniques were carried out by using observation, in-depth interviews, documentation, literature, and field notes. The steps of data analysis were carried out are data collection, data reduction, data presentation, and the conclusion stage. The results of the study were grouped into 3 answers: positive, neutral, and negative. In QP1 (Discipline) the numbers show the negative value was 61.1%, the neutral value was 3.9%, and the positive value was 17.3%. In QP2 (Hard work), it shows the negative value was 57.6%, the neutral value was 23%, and the positive value was 22.7%. In QP3 (Honest), it shows the negative value was 70.7%, the neutral value was 10.9%, and the positive value was 19.6%. In QP4 (Responsibility), it shows the negative value was 75.1%, the neutral value was 13.1%, and the positive value was 11.7%. In QP5, it shows the negative value was 77.7%, the neutral value was 10.4%, and 11.7%. Then from the interview results, there were six decrease factors of character values, they are facilities, parents, motivation, mindset, interaction, and learning models as well as media. The conclusion shows that during the online learning of the covid-19 pandemic, the students' character decrease in a negative direction.